PENGEMBANGAN KPOP PLUS BERBASIS DIGITAL UNTUK EFISIENSI DAN TRANSPARANSI LAYANAN ORTOTIK PROSTETIK DI RSUD SUMBERGLAGAH - Gatot Sunarto; Praviko Rahmadho; Bahana Rizka Winardi; Dea Septianiputri; Rahmat Apriyanto; Riska Permatasari (Bajang Institute, 2026)
Background: Access to orthotic–prosthetic services is often limited by administrative delays, patient unpreparedness, and inefficient workflows, particularly in developing countries. KPOP Plus (Integrated Orthotic–Prosthetic Service Channel) was developed at RSUD Sumberglagah to address these challenges by integrating two prior innovations: KPOP, a WhatsApp-based pre-visit consultation service, and SI-KEPO, a digital system for monitoring service progress. Methods: A quasi-experimental design with mixed-methods was employed in 2025, involving 250 purposively selected patients from a total of 880. Quantitative data were analyzed using descriptive statistics, paired t-tests, Wilcoxon tests, and Spearman correlations to assess administrative and medical readiness, staff efficiency, progress transparency, and patient satisfaction. Results: Implementation of KPOP and SI-KEPO significantly improved service outcomes: patient understanding of service processes increased from 3.21 to 4.61 (p<0.001), administrative readiness from 3.08 to 4.55 (p<0.001), overall satisfaction from 3.98 to 4.67 (p<0.001), and progress transparency from 28% to 86%. The integrated KPOP Plus platform is projected to reduce service delays by up to 90%, enhance workflow efficiency, and increase patient satisfaction to 97% in 2026. Achievements include nomination in the 2024 East Java Innovation Government Awards, administrative qualification in the 2025 KIPP–SINOVIK, and recognition as 2025 Top Innovation Kovablik Award. Conclusion: KPOP Plus provides a replicable, sustainable model for digital transformation in orthotic–prosthetic services, improving efficiency, transparency, and patient-centered care in public healthcare facilities.